Maternal and Paternal Authoritarian Parenting and Adolescents' Impostor Feelings: The Mediating Role of Parental Psychological Control and the Moderating Role of Child's Gender - Yosi Yaffe (MDPI AG, 2023)
Introduction: Recent systematic reviews about the impostor phenomenon unveil a severe shortage of research data on adolescents. The present study aimed at reducing this gap in the literature by investigating the association between maternal and paternal authoritarian parenting and impostor feelings among adolescents, while testing the mediating role played by parental psychological control and the moderating role of the child's gender in this context. Methods: Three hundred and eight adolescents took part in an online survey, in which they reported anonymously on their impostor feelings and their parents' parenting styles via several valid psychological questionnaires. The sample consisted of 143 boys and 165 girls, whose age ranged from 12 to 17 (M = 14.67, SD = 1.64). Results: Of the sample's participants, over 35% reported frequent to intense impostor feelings, with girls scoring significantly higher than boys on this scale. In general, the maternal and paternal parenting variables explained 15.2% and 13.3% (respectively) of the variance in the adolescents' impostor scores. Parental psychological control fully mediated (for fathers) and partially mediated (for mothers) the association between parental authoritarian parenting and the adolescents' impostor feelings. The child's gender moderated solely the maternal direct effect of authoritarian parenting on impostor feelings (this association was significant for boys alone), but not the mediating effect via psychological control. Conclusions: The current study introduces a specific explanation for the possible mechanism describing the early emergence of impostor feelings in adolescents based on parenting styles and behaviors.